Pengaruh Efisiensi dan Akuntabilitas Terhadap Efektivitas Anggaran dengan Transparansi Sebagai Variabel Mediasi pada Pemerintah Kota Jambi - Vema Rosalia; Afrizal Afrizal; Nela Safelia (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyse the influence of efficiency and accountability on budget effectiveness with transparency as a mediating variable in the Jambi City Government. Efficiency and accountability are key factors in budget management that can increase its effectiveness in this study. Transparency, as a supporting instrument, is believed to strengthen the relationship between efficiency, accountability, and budget effectiveness. This study examines all Regional Apparatus Organisations (OPD) in the Jambi City Government, which includes 27 OPDs involved in budget management, planning, reporting, and oversight. The method used is a quantitative approach with purposive sampling of employees directly involved in the process. Data was collected through questionnaires and analysed using Structural Equation Modelling (SEM) to test the direct and mediating relationships between the variables under study. It is hoped that the results of this study can contribute to improving efficiency, accountability, and transparency in regional budget management,as well as serving as a reference for the development of better regional financial management.